Instrumentos para uma gestão e fiscalização eficientes na execução contratual de um órgão público federal - Bastos, Rayane Ferreira (2021)
The present work has as its central question factors related to the performance of management and supervision of administrative contracts of continuous provision with exclusive dedication of outsourced services, within the scope of the Regional Administration Management in the State of Espírito Santo (GRA/ES). The problem, guide of this research, is how to sponsor essential and specific knowledge to the public servers designated for the functions of manager and tax of administrative contracts of outsourced services, in order to facilitate their contractual execution, avoiding the occurrence of irregularities, deviations, waste of funds of the Country Treasury. The main objective was to investigate the perceptions of the team of public servers, composed of a manager and two inspectors of administrative contracts, of the Regional Administration Management in the State of Espírito Santo (GRA/ES), about the main difficulties of the management and supervision of administrative contracts of continued services with exclusive dedication of outsourcing labor and propose suggestions for improvement for the performance of these professionals. The specific objectives were to identify vulnerabilities and suggestions for appropriate tools for effective, efficient and effective management and supervision. In theoretical terms, the characteristics of administrative contracts were initially discussed. Then, the concepts and applicability of the Theory of Loss Mitigation in administrative contracts were exposed, as well as the historical and conjuncture aspects of outsourcing contracts and the study on the management and supervision of administrative contracts. Regarding the methods and procedures, it urges to point out that the research has a qualitative descriptive type, the method for data collection was made through the application of a questionnaire with closed and open questions, sent to the team of public servers, in charge of the management and supervision of contracts, composed of a manager and two inspectors. The results indicate that the preparation, training and updating of public servers, the formulation and standardization of technical standards and procedures for managers and tax authorities are relevant and useful to the management and supervision of administrative contracts. The technological product developed was the elaboration of a set of proposals, components of a work plan, which aim to implement improvements in the management and supervision of GRA /ES, through training, improvement and the preparation of a manual of management and supervision of administrative contracts.